Vocabulary Learning Strategies Possessed by an Indonesian EFL Undergraduate Student During Authentic Novel Reading: A Qualitative Case Study - Hasnah Angreiny; Didik Santoso; Ernita Daulay (Universitas Islam Negeri Palopo, 2026)
Vocabulary acquisition constitutes one of the most demanding dimensions of English as a Foreign Language (EFL) learning, particularly within environments where authentic exposure to the target language is constrained. This qualitative case study investigates the vocabulary learning strategies (VLS) employed by an Indonesian EFL undergraduate student when engaging with an authentic literary text—specifically Franz Kafka's The Metamorphosis. Guided by the first research question regarding what vocabulary learning strategies the learner possesses during novel reading, the study draws upon Schmitt's (1997) taxonomic framework and Nation's (2001) cognitive processing model as theoretical foundations. Data were gathered through non-participant observation sessions and semi-structured in-depth interviews, supplemented by documentary evidence comprising the participant's written annotations and personal vocabulary records. Findings reveal that the participant employed a multi-layered repertoire of strategies, encompassing contextual inference, selective dictionary consultation, deliberate re-reading, marginal annotation, and personal vocabulary list construction. Analysis further demonstrates that strategy selection was governed by the learner's appraisal of a word's narrative significance, the frequency of its recurrence across chapters, and the extent to which lexical uncertainty disrupted overall reading comprehension. These findings underscore the inherently individualized and context-sensitive nature of vocabulary strategy use during sustained literary reading among EFL learners in Indonesian higher education. Pedagogical implications center on the need to foster explicit strategic awareness within EFL reading instruction, particularly through the integration of authentic literary texts as vehicles for vocabulary development.